The soluble cytoplasmic tail of CD45 regulates T‐cell activation via TLR4 signaling. Issue 12 (20th October 2021) - Puck, Alexander; Künig, Sarojinidevi; Modak, Madhura; May, Lara; Fritz, Pia; Battin, Claire; Radakovics, Katharina; Steinberger, Peter; Reipert, Birgit M.; Crowe, Brian A.; Stöckl, Johannes
Abstract: The soluble cytoplasmic tail of CD45 (ct‐CD45) is a cleavage fragment of CD45, that is generated during the activation of human phagocytes. Upon release to the extracellular space, ct‐CD45 binds to human T cells and inhibits their activation in vitro. Here, we studied the potential role of TLR4 as a receptor for ct‐CD45. Treatment of Jurkat TLR4/CD14 reporter cells with ct‐CD45 induced the upregulation of the reporter gene NFκB‐eGFP and could be blocked by inhibitors of TLR4 signaling. Conversely, ct‐CD45 did not promote the NFκB‐controlled eGFP induction in reporter cells expressing TLR1, TLR2, and TLR6 transgenes and did not lead to the activation of the transcription factors NFκB, AP‐1, and NFAT in a Jurkat reporter cell line expressing endogenous TLR5. Moreover, ct‐CD45 binds to recombinant TLR4 in an in vitro assay and this association was reduced in the presence of oxidized 1‐palmitoyl‐2‐arachidonyl‐sn‐glycero‐3‐phosphorylcholine. Blockade of TLR4 with mAb HTA125 partially reversed the ct‐CD45‐mediated inhibition of T‐cell proliferation. Interestingly, targeting of TLR4 with mAb W7C11 also suppressed T‐cell proliferation. In summary, the results of this study demonstrate that ct‐CD45 acts via a noncanonical TLR4 activation pathway on T cells, which modulates TCR signaling. Abstract : The soluble cytoplasmic tail of CD45 (ct‐CD45) is a cleavage fragment of CD45, which can bind to human T lymphocytes and inhibits their activation. The endogenous ligand ct‐CD45 acts as an immunoregulatory factor on T lymphocytes via noncanonical TLR4 activation. TLR4 signaling can modulate TCR signaling.